Welcome :: Homework Help and Answers :: Mathskey.com
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,369 questions

17,804 answers

1,438 comments

36,293 users

solve the system by the method using elimination 6x+3y=-12 and 6x+2y=-4

0 votes

solve the equation

asked Dec 4, 2013 in ALGEBRA 1 by payton Apprentice

1 Answer

0 votes

Elimination mehod

Given equations are 6x+3y = -12 ---------> (1)

6x+2y = -4 ---------> (2)

To eliminate the x value,subtract equation (2) from (1).

6x+3y = -12

6x+2y = -4

(-) (-)   (+)

_________

y = -8

Substitue the y value in (1).

6x+3*-8 = -12

6x-24 = -12

6x-24+24 = 12+24

6x = 12

6x/6 = 12/6

x = 2

Solution x =2, y =-8.

answered Dec 4, 2013 by william Mentor

Related questions

...